Aplikasi Antioksidan Tanaman Kecombrang Etlingera elatior terhadap Minyak Goreng Bekas: Antioxidant Application of Kecombrang Plant (Etlingera elatior) to Used Cooking Oil - Nurlaili Nurlaili; Ade Mardiana Damayanti; Chiara Sania Qonita; Muliyanti Muliyanti (Jurnal Sains dan Kesehatan, 2021)
Kecombrang (Etlingera elatior) is a plant from the Zingiberaceae family and is a plant used by the community as herbal medicine. This study aims to determine the antioxidant activity of the extracts of the leaves, floers and stems of E. elatior on used fried oil. Cooking oil has been used for frying 3 times. Treatment is done by mixing used cooking oil with extract (2 :1) at 50?C. The peroxide value of treated and untreated cooking oil was measured using the iodometric titration method. The decrease in the peroxide number produced in the E. elatior flower extract was 15,8%, the E. elatior stem extract was 55,3% and the E. elatior leaf extract was 72,8%. This study indicate that the E. Elatior extract can be used as good inhibitor of free radical activity.